Egypt far Western Desert basins petroleum charge system as defined by oil chemistry and unmixing analysis. (November 2016) - Abrams, Michael A.; Greb, Matthias D.; Collister, James W.; Thompson, Melissa
Abstract: Source rock analysis and maturity modeling in Egypt's Far Western Desert basins indicates that several Jurassic and Cretaceous petroleum source rocks could be mature and expelling hydrocarbons over much of the area. Highly variable oil characteristics suggest that more than one charge system may be present. Reservoir crude oil chemistry indicates that the fluids originated from a single source facies generated over a wide range of organic maturity. Secondary alteration mechanisms include water washing, biodegradation, and evaporative fractionation. Crude oils in the upper reservoirs tend to be most affected by biodegradation and water washing. Condensates and light crude oils in the deepest reservoirs appear to be the residual phase from evaporative fractionation. The broad variation in fluid properties and chromatogram character can be attributed to a multi end-member mixing system: early mature waxy oil, later high maturity volatile oil, low level biodegradation, migrated phase evaporative fractionation, and residual phase evaporative fractionation. A statistical "unmixing" algorithm was used to determine end-member compositions and relative mixing proportions for each crude oil sample. Remigration and mixing of the products from multi-phase generation and alteration results in complex reservoir fluid compositions, such that no single reservoired oil represents a compositional end-member, rather the oil samples are mixtures of various amounts of multiple end-members. Mixing proportions show regional trends and variations in different reservoirs within a single field. The crude oil geochemical data and unmixing analysis support a complex charge history from a single source rock, rather than mixing of oils from two source rocks. Highlights: Variable oil characteristics suggest more than one charge system may be present but oil chemistry indicates a single source facies generated over wide range of organic maturity. A statistical "unmixing" algorithm was used to determine end-member compositions and relative mixing proportions for each crude oil sample. The broad variation in fluid properties can be attributed to a multi end-member mixing system. The remigration and mixing of multi-phase generation and alteration results in a reservoir fluid from multiple processes, with no one reservoir oil being an end member. Examination of mixing proportions shows regional trends and changes within different reservoirs of a single field.